The Circadian Neuropeptide PDF Signals Preferentially through a Specific Adenylate Cyclase Isoform AC3 in M Pacemakers of Drosophila - Duvall, Laura B. (Public Library of Science, 2012)

(untitled)
The neuropeptide Pigment Dispersing Factor (PDF) is essential for normal circadian function in Drosophila. It synchronizes the phases of M pacemakers, while in E pacemakers it decelerates their cycling and supports their amplitude. The PDF receptor (PDF-R) is present in both M and subsets of E cells. Activation of PDF-R stimulates cAMP increases in vitro and in M cells in vivo. The present study asks: What is the identity of downstream signaling components that are associated with PDF receptor in specific circadian pacemaker neurons? Using live imaging of intact fly brains and transgenic RNAi, we show that adenylate cyclase AC3 underlies PDF signaling in M cells. Genetic disruptions of AC3 specifically disrupt PDF responses: they do not affect other Gs-coupled GPCR signaling in M cells, they can be rescued, and they do not represent developmental alterations. Knockdown of the Drosophila AKAP-like scaffolding protein Nervy also reduces PDF responses. Flies with AC3 alterations show behavioral syndromes consistent with known roles of M pacemakers as mediated by PDF. Surprisingly, disruption of AC3 does not alter PDF responses in E cells—the PDF-R(+) LNd. Within M pacemakers, PDF-R couples preferentially to a single AC, but PDF-R association with a different AC(s) is needed to explain PDF signaling in the E pacemakers. Thus critical pathways of circadian synchronization are mediated by highly specific second messenger components. These findings support a hypothesis that PDF signaling components within target cells are sequestered into “circadian signalosomes,” whose compositions differ between E and M pacemaker cell types.